Comparison of Outcomes Between Mometasone Furoate Intranasal Spray and Oral Montelukast in Patients with Allergic Rhinitis - Bhattachan, Sushma; Neupane, Yogesh; Pradhan, Bibhu; Thapa, Naramaya (Journal of Nepal Health Research Council, 2020)
Background: Allergic rhinitis is a common ailment with rising trend and worldwide prevalence of some 400 million. Methods: This prospective randomized crosssectional study was done at the Department of Otorhinolaryngology and Head and Neck Surgery, Tribhuvan University, Teaching Hospital, Kathmandu, Nepal from June 2016 to August 2017. They were randomly assigned to two groups by lottery method. Group A received mometasone furoate intranasal spray and Group B received oral montelukast for a total duration of one month. Prior to starting medication and one month after medications, total nasal symptom score was documented. Statistical analysis was done using SPSS version 18. Results: Total of 126 patients between 16 to 52 years were enrolled in the study. The mean duration of symptoms was 3.93 years. The mean value of serum total IgE was 833.49 IU/ml. The mean pre and post medication score for mometasone furoate intranasal spray group was 16.32 and 5.44 respectively, which was significant. Similarly, the mean pre and post medication score for oral montelukast group was 15.24 and 7.87 respectively which was also found to be significant. Comparing the means of scores for both the groups, mometasone furoate was found to be more effective than oral montelukast. Conclusions: Both mometasone furoate intranasal spray and oral montelukast were effective in the treatment of patient with allergic rhinitis. Oral montelukast can therefore be used as a first line treatment for patients with allergic rhinitis. Keywords: Allergic rhinitis; mometasone furoate intranasal spray; montelukast; serum total IgE; total nasal symptom score.